Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Peningkatan Penjualan Pada PT. Alam Jaya Wirasentosa Sibolga - Agustina Tanjung (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine and analyze the effect of Service Quality and Product Quality on Sales Increase at PT. Alam Jaya Wirasentosa Sibolga. The research employed a quantitative method with an associative approach. The population consisted of all consumers of PT. Alam Jaya Wirasentosa Sibolga, with a total sample of 57 respondents. Data analysis techniques included classical assumption tests, correlation analysis, coefficient of determination, multiple linear regression, and hypothesis testing using t-test and F-test with the assistance of SPSS version 26.0. The results showed that partially Service Quality had a correlation value of 0.726 and Product Quality had a correlation value of 0.688 with Sales Increase, both categorized as strong and significant. Simultaneously, the coefficient of determination (R²) value of 0.634 indicates that 63.4% of the variation in Sales Increase can be explained by Service Quality and Product Quality, while the remaining percentage is influenced by other factors outside this study. The multiple linear regression equation obtained was Y = 3.307 + 0.525X1 + 0.424X2. The results of the t-test and F-test indicate that Service Quality and Product Quality have a positive and significant effect both partially and simultaneously on Sales Increase. Therefore, improving service quality and product quality is an important strategy to enhance company sales performance.